Determining the heat flux distribution of laminar plasma jet impinging upon a flat surface: An indirect method using surface transformation hardening. (March 2018) - Xiang, Yong; Yu, Deping; Liu, Fangyuan; Lv, Cheng; Yao, Jin
Highlights: An indirect method was proposed for determining the heat flux distribution of laminar plasma jet ( q H ( r ) ). The q H ( r ) was obtained by experimental and numerical analysis of the surface transformation hardening. The proposed method has little limitations on the axial distance and the power level of the laminar plasma jet (LPJ). The axial gradient of nitrogen LPJ's heat flux is less than 50% drop at an axial distance of 100 mm. Abstract: Laminar plasma jet (LPJ) is a promising high energy beam for various engineering applications. However, there lacks of a method for measuring the heat flux distribution of the LPJ impinging upon a flat surface ( q H ( r ) ), with high accuracy, little limitations on the axial distance from the torch exit and the power of the LPJ. Therefore, this paper proposes an indirect method for determining q H ( r ) using surface transformation hardening. It makes use of the fact that when LPJ is used in the surface transformation hardening of a ferrous material, the size of the heat affected zone is directly correlated with the heat flux distribution. It combines the experiment and numerical simulation on the heat transfer process of the surface transformation hardening to indirectly obtain q H ( r ) at a certain axial distance from the torch exit. The proposed method was used to determine q H ( r ) of the nitrogen LPJ generated by a customized laminar plasma torch at different axial distance from the torch exit. It was found that the proposed method exhibits high accuracy through benchmarking with the results obtained by numerical simulation and by direct measurement using the double calorimetric technique reported in literature. Furthermore, the proposed indirect method has little limitations on the axial distance from the torch exit and the power level of the LPJ. In addition, it was found that that axial gradient of the LPJ's heat flux is low, with less than 50% drop after an axial distance of 100 mm from the torch exit. Finally, the determined q H ( r ) was directly verified by the numerical simulations and experimental observation on plasma surface transformation hardening of a different ferrous material.